An Analysis of Pedagogical Competence of Pre-Service Teacher Professional Education (PPG-Prajabatan) Teacher - Nurlailah Qadrianty; Syarifuddin Dollah; A. Muliati (PT ARRUS Intelektual Indonesia, 2024)
This research aims to discover the teacher’s pedagogical competence and the ways the teacher applied the pedagogical competence in the classroom. This research was conducted under the qualitative case study design. The subject of this research involved an EFL teacher in SMP Negeri 2 Pangkep using purposive sampling. The data were gathered from classroom observations and interviews. The findings showed that the teacher demonstrates a fair level of competence in understanding students’ characteristics, learning theories and approaches, curriculum development, assessment and evaluation development, utilizing technology, and learning reflection while showing a poor level of competence in creating engaging learning activities and developing into students' potential. However, the teacher excels in communication with students. The findings also showed the ways the teacher applied the pedagogical competence through various practices based on nine pedagogical competencies: understanding the students’ characteristics, understanding theories and learning approaches, developing curriculum, developing assessments and evaluations, utilizing technology in learning, communicating with the students, developing engaging and educative learning activities, developing students’ potential, and learning reflections. However, there are areas for improvement, particularly in creating engaging learning activities and identifying and developing students' potential. In conclusion, the teacher implements strategies to maintain a supportive learning environment based on the teacher’s pedagogical competence. These findings underscore the importance of comprehensive pedagogical development to enhance teaching effectiveness.